Cross-Cultural Experiences of the Insulted and Injured Women in Sidhwa’s An American Brat - Gautam, Mani Bhadra (Multi-Disciplinary Explorations: The Kasthamandap College Journal, 2024)
Bapsi Sidhwa collects narratives of insulted and injured people, especially the women, who are victim of the distorted cultural shifts. Sidhwa in this novel exposes the pain and suffering of women through the experiences and memories of Feroza. She was humiliated from numbers of people and one among them is an American officer’s rudeness who forced to marry with her uncle Manek. He threatened to take a legal action if they live together without marriage. She faces the numbers of challenges in America and she has to reach up to the decision of being back to Lahore in Pakistan where she could feel safe. Objective of this paper is to show the difficulties to adjust in the new cultural values that one cannot adopt easily. Finding of this paper is that it is better to be flexible ourselves if we shift to the new geographical location and the new cultural practices zone. Cultural rigidity is a main cause of human suffering. The novel is studied from gynocentric perspective and this paper is prepared in qualitative method of women centered study. Theoretical support is taken from Gaur, Menon, Bhasin, Das and Butalia to prepare this paper.